Optimalisasi Infrastruktur Teknologi Informasi untuk Mendukung Stabilitas Operasional Perusahaan pada PT Kreasi Utama Palembang - Fitria Azzahra; Arsika; Yuniar Antika Sari; Fenny Purwani (Berkah Tematik Mandiri, 2026)
Information Technology (IT) infrastructure plays an important role in supporting the sustainability of a company's operational activities. The availability of reliable networks, hardware, software, and information security systems is a key factor in maintaining service stability and work productivity. PT Kreasi Utama Palembang, as a company that utilizes information technology in its operational processes, needs to ensure that its IT infrastructure is capable of optimally supporting business requirements. This study aims to analyze the condition of the IT infrastructure implemented at PT Kreasi Utama Palembang and to formulate optimization strategies to improve the company's operational stability. The research employed a descriptive qualitative method, with data collected through observation, interviews, documentation, and literature review. Data analysis was conducted using the SWOT (Strengths, Weaknesses, Opportunities, and Threats) method to identify internal and external factors affecting the management of the company's IT infrastructure. The results indicate that the company's IT infrastructure has been able to support operational activities; however, several weaknesses remain, including the absence of a real-time network monitoring system, non-automated data backup mechanisms, the lack of a backup internet connection, and limitations in information security systems. Based on the SWOT analysis, the recommended optimization strategies include implementing network monitoring systems, adopting automated cloud-based backups, strengthening network security, utilizing internet failover connections, and performing periodic hardware upgrades. The implementation of these recommendations is expected to enhance the company's operational stability in a sustainable manner.